Effective EFL Teachers: Non-English Department Students’ Perspectives - Lena Febriana; Daflizar; Musdizal (Institut Agama Islam Negeri Palopo, 2025)
This study investigated the perspectives of non-English major students at an Islamic institution of higher education in Indonesia regarding the attributes of effective English as a Foreign Language (EFL) lecturers. The study aimed to identify key factors students consider important in learning English and to explore teaching strategies that enhance learning effectiveness. A quantitative survey method was employed, involving 300 students from various non-English majors. Data were analyzed using ANOVA to examine differences among groups, followed by post-hoc Tukey tests to identify specific group differences. The results indicated that students rated communication skills (M = 4.52, SD = 0.61) and teaching methods (M = 4.47, SD = 0.65) as the most important attributes of effective EFL lecturers. These were followed by lecturer credibility (M = 4.32, SD = 0.68) and knowledge of English (M = 4.29, SD = 0.70). Additional influential factors included the quality of interpersonal relationships between lecturers and students, fairness in assessment, and organization and preparation in teaching. Furthermore, the study found that the strategic use of the mother tongue (L1) in instruction increased students' confidence in using English. The implications of this study underscore the importance of flexible teaching approaches that accommodate diverse learning styles. The use of interactive methods, educational technology, and clear material delivery can significantly enhance the effectiveness of English language teaching in higher education settings.